Assistance for Packaging, Branding and Marketing through Digital Media with Asset Based Community Development Approach in Sombo Village, Lumajang District - Nissa, Kharisma Alfun; Asrohah, Hanun (Universitas Ibn Khaldun, 2025)
Micro, small and medium enterprises (MSMEs) have a role in economic development, but over time face challenges in business development and marketing. This research aims to help micro, small and medium enterprises (MSMEs) in Sombo Village, Lumajang Regency through assistance in the development of businesses run in the process of packaging, branding, and online marketing. The Asset-Based Community Development approach was used with five stages: inculturation, discovery, design, define, and reflection. The mentoring targets are producers of taro chips, bananas, belantik goats and sheep. This activity was carried out using methods including observation, interviews, and direct assistance. The results of the activity include recommendations for using the latest packaging with the creation of a hygienic, safe and modern brand logo for traders as a packaging process and business branding with the production of chips increasing from 36-200 pcs / week to 50-240 pcs / week. While for belantik is assistance for branding and marketing of goats and sheep by utilizing social media with sales results increasing to 2 times. This was done as a marketing tactic to attract customers' attention which had an impact on increasing sales. The output of the activity is in the form of instructions for making packaging labels, ready-to-use designs, and branding social media accounts. The resulting positive impacts include increased product competitiveness, local economic empowerment, and expansion of marketing networks and local economic development. The development of brand identity through unique logos and packaging and the application of digital marketing strategies are significant novelties in this research.